2010
DOI: 10.2217/fnl.10.30
|View full text |Cite
|
Sign up to set email alerts
|

Histamine neuronal system as a therapeutic target for the treatment of cognitive disorders

Abstract: Much has been learned over the past 20 years about the role of histamine as a neurotransmitter. This brief article attempts to evaluate the progress accomplished in this field, and discusses the therapeutic potential of the H3 receptor (H3R). All histaminergic neurons are localized in the tuberomammillary nucleus of the posterior hypothalamus and project to almost all regions of the CNS. Histamine exerts its effect via interaction with specific receptors (H1R, H2R, H3R and H4R). Antagonists of both H1R and H2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 121 publications
(129 reference statements)
2
3
0
Order By: Relevance
“…Indeed, the histaminergic system can implement many functions, including the arousal state, brain energy metabolism, locomotor activity, neuroendocrine, autonomic, and vestibular functions, feeding, drinking, sexual behavior, and analgesia, presumably by engaging independent subpopulations of histaminergic neurons according to the brain regions required for a particular behavioral outcome. Consistent with this hypothesis, heterogeneity within the histaminergic neuronal population in response to stress (Miklos and Kovacs, 2003 ) and pharmacological stimulations was recently reported (Blandina et al, 2010 ; Passani and Blandina, 2011 ).…”
Section: Histamine Is Involved In Many Brain Functionssupporting
confidence: 61%
“…Indeed, the histaminergic system can implement many functions, including the arousal state, brain energy metabolism, locomotor activity, neuroendocrine, autonomic, and vestibular functions, feeding, drinking, sexual behavior, and analgesia, presumably by engaging independent subpopulations of histaminergic neurons according to the brain regions required for a particular behavioral outcome. Consistent with this hypothesis, heterogeneity within the histaminergic neuronal population in response to stress (Miklos and Kovacs, 2003 ) and pharmacological stimulations was recently reported (Blandina et al, 2010 ; Passani and Blandina, 2011 ).…”
Section: Histamine Is Involved In Many Brain Functionssupporting
confidence: 61%
“…This was also confirmed by the marked decrease in the gene expression of caspase-3 and caspase-9. These findings matched that of Blandina et al (2010), who found that histamine protects cerebral cortex and hippocampus neurons from damage caused by kainic acid.…”
Section: Discussionsupporting
confidence: 91%
“…H 3 receptors are mostly presynaptic, expressed as autoreceptors on histaminergic neurons involved in the negative feedback control of histamine levels (Arrang et al, 1983; Hough & Rice, 2011), while H 3 heteroreceptors on postsynaptic nonhistaminergic neurons also regulate negatively the release of neurotransmitters, such as ACh, dopamine, 5‐HT, and noradrenaline (Blandina, Munari, Giannoni, Mariottini, & Passani, 2010; Gemkow et al, 2009; Giannoni et al, 2010). Since the cloning of H 3 receptors (Lovenberg et al, 1999), there has been an increased interest within the pharmaceutical industry in developing ligands for this receptor to target several diseases, including neuropathic pain.…”
Section: Histamine Receptor Ligands and Neuropathic Painmentioning
confidence: 99%
“…In line with this, electrophysiological studies performed in anaesthetized animals indicated that, after systemic administration, GSK189254 dose‐dependently decreased both evoked and spontaneous firing of wide dynamic range neurons in neuropathic, but not sham‐operated rats (McGaraughty et al, 2012). However, analgesia induced by the blockade of the H 3 receptor can also be mediated via H 3 heteroreceptors that regulate other neurotransmitters' release; the blockade of the H 3 receptor is known to increase the release of ACh, dopamine, 5‐HT, noradrenaline, and SP in the CNS (Blandina et al, 2010; Gemkow et al, 2009; Giannoni et al, 2010).…”
Section: Histamine Receptor Ligands and Neuropathic Painmentioning
confidence: 99%